UKRAINE AND NATO (NORTH ATLANTIC TREATY ORGANIZATION): CONCERNING THE QUESTION OF HISTORIOGRAPHY OF THE INVESTIGATION INTO THE PROBLEM - Білоус, Л. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
In this article some aspects of relations between Ukraine and NATO, to analysis of which great attention of home scientists is paid, are explained.